(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the reforms in the field of religious tolerance carried out in our country, the opportunities given to the population in this context, the friendly relations between our multi-ethnic people, the current actions of international terrorist and extremist organizations that use these opportunities for their malicious intentions, and the resulting social, economic, spiritual and criminogenic consequences are studied.